Pressupostos do direito intertemporal no processo civil - Soares, André Mattos (2007)
The phenomenon regarding law conflicts in time, claiming the application of principles and rules concerning intertemporal law, is directly related to validity and efficiency law institutes, the first necessary to the checking of the fact s period, if past, during or future and the second concerning the investigation of the rule which effects will be applied to a certain factual situation. As it is inherent to natural human feelings of inviolability to the past and considering the actual evolutional stage of man, the non retroactivity of laws and the respects to acquired rights must be the rule in the juridical ordination in general. And thus it is in the Brazilian system, which, furthermore, proscribes in a constitutional headquarter the violation to acquired rights, to perfect juridical act and to a sentenced thing. In spite of the father law having suffered the influence of subjective and objective doctrines, from which, are respectively enhanced the figures of Gabba and Roubier, and although the notion of the juridical situation exceeds that of acquired rights, the flows are more or less equivalent in general terms, for means of practical results. On the other hand, the ways of law projection in time (retroactivity, immediate efficiency and ultra activity) must be understood in their right limits, especially as to incidence of novel diploma on the future effects of the precedent act, circumstance to characterize the simple immediate law effect, from which, however we protect the acquired law. The Magna Carta, yet, does not obstruct the retrooperancy of law, for which effect it demands the expression of a new law, once the acquired right is observed (which embraces the concepts of perfect juridical act and judged thing), limitation applied to public order and constitutional amendments. The exceptional violation to acquired rights is only allowed if required by the principle of dignity of the human being. On the other hand, the procedural law, is submitted to the general regime of intertemporal right mentioned in the Constitution and in the Introduction Law, from where, at first, it has no retroactive effect, not reaching the procedural acts improved under the previous regime, possessing, instead, immediate efficiency regarding the pending processes. In spite of the applicability of the general regulation, the process is of such complexity that the current new law effect presents particularities originated from the necessary harmony of the procedural acts, of the obedience to the procedural principles, of the peculiarity of certain procedural institutes consequences which might postpone or exclude the prompt efficiency of the normative novel command